(untitled) (Revista Electrónica REDINE, 2018)
This article research results show that in line with the Plan of Strategic Management 2012 - 2017 from the Lisandro Alvarado University (UCLA), a Virtual Learning Environment (VLE) was designed as a mechanism for innovation to dictate the course of University Initiation (CIU) to all new students Agroindustrial Engineering Program of the Dean of Agriculture, in this case show the Induction Course Moodle Platform. Today, universities and teachers must constantly innovate in terms of new forms of teaching is how the teaching-learning process becomes more dynamic and better attention from the students is obtained as to who is entering strategies different from what they are accustomed to using, this course will enable them to understand and navigate when learning in a Moodle course under distance learning or distance learning easier and can handle each of the tools you have.